Powers of the President as Chief Executive in Determining the Number of State Ministries Based on the 1945 Constitution - Mustomi, Otom; Siregar, Hamdan Azhar (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Powers of the President as Chief Executive in Determining the Number of State Ministries According to the 1945 Constitution. With the amendments to the 1945 Constitution, the President and his partner, namely the Vice President, are directly elected by the people. And the pair that gets the most votes will be sworn in as President and Vice President. Thus began a new chapter in a government led by the President and Vice President. In addition to the President being assisted by the Vice President, based on article 17 paragraph (1) of the 1945 Constitution "The President is assisted by state ministers.". Whereas paragraph (2) based on the first amendment to the 1945 Constitution contains "Ministers are appointed and dismissed by the President" which is actually the same as the contents of the 1945 Constitution before the amendment. The only difference is the word "dismissed" with the change to "dismissed." Then in paragraph (3) of the 1945 Constitution before the change, the contents were "Those ministers lead government departments" were changed to "Each minister is in charge of certain affairs in government." That the article meant that only ministers were in charge of certain affairs/certain tasks. In addition, there is the addition of one paragraph to the third amendment to the 1945 Constitution, namely paragraph (4) which contains "The formation, change and dissolution of state ministries is regulated in law." This is intended to form new departments and dissolve departments that need to be regulated by law so that it is not too easy to dissolve them. Based on the addition of paragraph (4) in the third amendment to article 17 LJIJD 1945, the President is limited in terms of how to form, change and dissolve state ministries. If the state ministries are regulated in law, this will limit the prerogative of the President as the head of the executive power in determining the state ministries, where apart from having the right to determine the ministers who lead the departments, the President also has the right to determine the departments